2015
DOI: 10.1016/j.ces.2015.05.025
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic performance of cobalt–silica catalyst for Fischer–Tropsch synthesis: Effects of reaction rates on efficiency of liquid synthesis

Abstract: A one-dimensional pseudo-homogeneous mathematical model of a fixed bed reactor for Fischer-Tropsch (FT) synthesis was developed for the flow of simulated N 2 -rich syngas over an in-house cobalt-silica catalyst. This study aims at improving the efficiency of FT synthesis by maximizing the liquid productivities and selectivity, as well as maximizing the syngas conversion and minimizing the methane formation. The developed model predicts the fraction of the reactants and products along the reactor bed length. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…From the predicted results, it was found that at high temperature conditions, especially when T ≥ 528 K, the predicted results were not in good agreement with the measured data in which the predicted values presented a higher relative residual than those obtained at a lower temperature. However, the results presented in the past studies [33][34][35][36]52] revealed that with the narrower temperature range, for instance when T changes between 500-528 K,…”
Section: Wgs Reaction Rate Mechanismmentioning
confidence: 94%
“…From the predicted results, it was found that at high temperature conditions, especially when T ≥ 528 K, the predicted results were not in good agreement with the measured data in which the predicted values presented a higher relative residual than those obtained at a lower temperature. However, the results presented in the past studies [33][34][35][36]52] revealed that with the narrower temperature range, for instance when T changes between 500-528 K,…”
Section: Wgs Reaction Rate Mechanismmentioning
confidence: 94%
“…To achieve an optimum in performance for the whole process, the mathematical development of the kinetics and the reactor model are essential. Also, the details of the products' distribution, selectivity and reactants conversion should be achieved by the developed mathematical model 15 . By modelling and optimizing the reactor's operation, it is possible in many cases to achieve significantly enhanced throughput;…”
Section: Introductionmentioning
confidence: 99%
“…To achieve an optimum in performance for the whole process, the mathematical development of the kinetics and the reactor model are essential. Also, the details of the products’ distribution, selectivity, and reactants conversion should be achieved by the developed mathematical model . By modeling and optimizing the reactor’s operation, it is possible in many cases to achieve significantly enhanced throughput, better and more consistent product quality, rising conversion and selectivity, as well as a significant effect on the scaling up of the processes from the laboratory to production scale.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The large specific surface area (ca. 757 m 2 g −1 ) of activated biochar favored a higher dispersion of Ru nanoparticles (>70%) compared to other usual support such as Al 2 O 3 (43%) and SiO 2 (17%), which may account for the effective catalytic performance [86]. Later on, the same authors observed a high CH 4 selectivity (98%) and a CO conversion of 100% and also an excellent stability for a period of at least 100 h on stream over the Ru activated biochar catalysts [87].…”
Section: Fischer-tropsch Synthesismentioning
confidence: 97%